2022
DOI: 10.26434/chemrxiv-2022-x5wgq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Versatile DIY Route for Incorporation of a Wide Range of Electrode Materials into Rotating Ring Disk Electrodes

Abstract: Rotating ring disk electrodes (RRDEs) are a powerful and versatile tool for mechanistically investigating electrochemical reactions at electrode surfaces, particularly in the area of electroanalysis and catalysis. Despite their importance only limited electrode materials (typically glassy carbon, platinum and gold) and combinations thereof are available commercially. In this work we present a method employing 3D printing in conjunction with machined brass components to produce housing which can accommodate any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Indeed, although we decided to use SECM because of its steadystate and imaging capabilities, short time scale for species detection, and previous experience in our laboratory with methods for ROS detection, 50 there is no reason why the presented methodology cannot be deployed using other techniques such as the rotating ring-disk electrode (RRDE), provided a suitable disk electrode is available. 63 Many laboratories in countries with limited resources may not have ESR instrumentation available, but it is common to find wellestablished electrochemical facilities elsewhere. Thus, we hope these findings will encourage more quantitative and informed mechanistic explorations of the role of • OH mediated oxidation processes on Fenton systems and on electrode surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although we decided to use SECM because of its steadystate and imaging capabilities, short time scale for species detection, and previous experience in our laboratory with methods for ROS detection, 50 there is no reason why the presented methodology cannot be deployed using other techniques such as the rotating ring-disk electrode (RRDE), provided a suitable disk electrode is available. 63 Many laboratories in countries with limited resources may not have ESR instrumentation available, but it is common to find wellestablished electrochemical facilities elsewhere. Thus, we hope these findings will encourage more quantitative and informed mechanistic explorations of the role of • OH mediated oxidation processes on Fenton systems and on electrode surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggested that quantification of the true concentration of OH • generated from water oxidation via EC-EPR is problematic. The use of different cell geometries, such as flow cells and/or rotating disk electrodes, 62 could be beneficial to minimize fouling events and prevent further oxidation of DMPO-OH • , as the product is swept away from the electrode surface. Further investigations are required.…”
Section: ■ Conclusionmentioning
confidence: 99%